ANALISA PENGELOLAAN ALOKASI ANGGARAN DANA DESA BESERTA FAKTOR PENGHAMBAT DAN PENDUKUNG PADA BADAN USAHA MILIK DESA (STUDI KASUS DESA BABAKSARI, KECAMATAN DUKUN, KABUPATEN GRESIK) - Muhammad Afifudin Zuhri; Sri Muljaningsih (LPPM Universitas Djuanda Bogor, 2022)
The main objective of implementing regional autonomy is to improve public services and improve the regional economy. a policy called the Village Fund Allocation (ADD) to support all sectors in society. ADD is a form of financial relationship between levels of government. BUMDesa as a social institution has a contribution as a provider of social services while its function as a commercial institution means that BUMDesa aims to seek profit through offering local resources (goods and services) to the market. In Babaksari village, Dukun sub-district, Gresik Regency, BUMDes activities have not run optimally. Although in the end this BUMDes can get quite a large profit every year. The purpose of this study is to analyze the management of village fund budget allocations along with the inhibiting and supporting factors in Village-Owned Enterprises (Case study of Babaksari Village, Dukun District, Gresik Regency). This type of research is descriptive qualitative research. Data collection techniques are using: Observation, Interview, Documentation by collecting village documents. The results of this study show that at the planning stage ADD has been carried out in a participatory manner through village deliberations, but the level of community participation is still low. Then the stage of implementing activities on the realization of the use of ADD for community empowerment in Babaksari village is Rp. 49.319.785.472.05,-. BUMDesa Mekar Sari itself provides a savings and loan service program that aims to increase family income with independence. At the accountability stage, based on the observations of the researcher, there has not been any accountability to the community. Then the inhibiting factor in the management of ADD in Babaksari Village is the low community participation and the supporting factor, namely human resources, is considered good enough to lead to good village management. Kata kunci: Allocation of Village Funds, BUMDes, and Community Empowerment.